Physicochemical and microbiological properties of yogurt made with microencapsulation probiotic starter during cold storage - Evy Rossi; FAJAR RESTUHADI; RASWEN EFENDI; YOSSIE KHARISMA DEWI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rossi E, Restuhadi F, Efendi R, Dewi YK. 2021. Physicochemical and microbiological properties of yogurt made with microencapsulation probiotic starter during cold storage. Biodiversitas 22: 2012-2018. This study's purposes were to characterize probiotic properties, identify strains of K12.1, produce a microencapsulated starter (MS) for yogurt, and evaluate yogurt's microbiological quality during storage refrigerated temperatures. This research was conducted experimentally using isolate was further identified based on 16S rRNA gene sequence analysis.  The identified strain and Streptococcus thermophilus were microencapsulated using sago starch and whey isolate protein (1:1 w/w) for yogurt starter.  The starter was added as much as 1, 3, 5, or 7% (v / v), then incubated for 18 hours at 37°C. The best yogurt was evaluated for its microbiological quality at refrigerated temperature for 0, 7, 14, 21, and 28 days.  The results showed that K12.1 isolate with probiotic characteristics was Lactobacillus plantarum VP3.3. The microencapsulation starter concentration affected acidity, total acid, total lactic acid bacteria (LAB), viscosity, and total solids. The use of 7% microencapsulation starter of Lactobacillus plantarum VP-3.3 and Streptococcus thermophilus gave the best yogurt, with a pH value 4.36, total lactic acid 0.99%, total LAB 10.00 log CFU mL-1, viscosity 546.37 cP, and total solids 10.40%. The total amount of LAB in yogurt stored during cold temperature for 28 days still meets the probiotics standards (9.98 log CFU/mL).